Family history of diabetes and risk of SARS‐COV‐2 in UK Biobank: A prospective cohort study. Issue 4 (11th July 2021) - Jani, Bhautesh Dinesh; Nicholl, Barbara I.; Hanlon, Peter; Mair, Frances S.; Gill, Jason MR.; Gray, Stuart R.; Celis‐Morales, Carlos A.; Ho, Frederick K.; Lyall, Donald M.; Anderson, Jana J.; Hastie, Claire E.; Bailey, Mark ES.; et al.
Abstract: Introduction: The aim of this study was to determine risk of being SARS‐CoV‐2 positive and severe infection (associated with hospitalization/mortality) in those with family history of diabetes. Methods: We used UK Biobank, an observational cohort recruited between 2006 and 2010. We compared the risk of being SARS‐CoV‐2 positive and severe infection for those with family history of diabetes (mother/father/sibling) against those without. Results: Of 401, 268 participants in total, 13, 331 tested positive for SARS‐CoV‐2 and 2282 had severe infection by end of January 2021. In unadjusted models, participants with ≥2 family members with diabetes were more likely to be SARS‐CoV‐2 positive (risk ratio‐RR 1.35; 95% confidence interval‐CI 1.24–1.47) and severe infection (RR 1.30; 95% CI 1.04–1.59), compared to those without. The excess risk of being tested positive for SARS‐CoV‐2 was attenuated but significant after adjusting for demographics, lifestyle factors, multimorbidity and presence of cardiometabolic conditions. The excess risk for severe infection was no longer significant after adjusting for demographics, lifestyle factors, multimorbidity and presence of cardiometabolic conditions, and was absent when excluding incident diabetes. Conclusion: The totality of the results suggests that good lifestyle and not developing incident diabetes may lessen risks of severe infections in people with a strong family of diabetes. Abstract : Our aim was to determine risk of severe SARS‐CoV‐2 (infection associated with hospitalization/mortality) in those with family history of diabetes. Using UK Biobank data, the findings suggest that having ≥2 family members with diabetes is associated with higher risk of SARS‐CoV‐2 infection and severe infection, but that such risk may be attenuated by better lifestyle, and by avoiding development of diabetes.